(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The article examines the macroeconomic factors for improving the rating in the Global Innovation Index (GII), in particular, based on the analysis of the methodological framework, groups data sources and macroeconomic indicators of the GII, and identifies quantitative indicators of the index.